2011
DOI: 10.1212/wnl.0b013e318227b164
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, blinded trial of weekend vs daily prednisone in Duchenne muscular dystrophy

Abstract: Objective: To perform a double-blind, randomized study comparing efficacy and safety of daily and weekend prednisone in boys with Duchenne muscular dystrophy (DMD). Methods:A total of 64 boys with DMD who were between 4 and 10 years of age were randomized at 1 of 12 centers of the Cooperative International Neuromuscular Research Group. Efficacy and safety of 2 prednisone schedules (daily 0.75 mg/kg/day and weekend 10 mg/kg/wk) were evaluated over 12 months.Results: Equivalence was met for weekend and daily dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
127
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(135 citation statements)
references
References 36 publications
(36 reference statements)
6
127
1
1
Order By: Relevance
“…Later studies have demonstrated that different drugs with an equivalent dose show similar effects: prednisone or prednisolone 0.75mg/Kg daily (Level of evidence: 1A, Class of Recommendation: A) 35 or deflazacort 0.9 to 1mg/Kg daily (Level of evidence: 3C, Class of Recommendation: C) 44,45 . Several different drug regimens have been evaluated, but not as extensively as the above daily schemes 44,45,46,47,48 . These different regimens aim to minimize side effects and/or improve the treatment adherence.…”
Section: Which Glucocorticoid Should Be Prescribed and What Dose Is Rmentioning
confidence: 99%
“…Later studies have demonstrated that different drugs with an equivalent dose show similar effects: prednisone or prednisolone 0.75mg/Kg daily (Level of evidence: 1A, Class of Recommendation: A) 35 or deflazacort 0.9 to 1mg/Kg daily (Level of evidence: 3C, Class of Recommendation: C) 44,45 . Several different drug regimens have been evaluated, but not as extensively as the above daily schemes 44,45,46,47,48 . These different regimens aim to minimize side effects and/or improve the treatment adherence.…”
Section: Which Glucocorticoid Should Be Prescribed and What Dose Is Rmentioning
confidence: 99%
“…The first clinical trial in DMD demonstrating efficacy of prednisone occurred in 1974 [30]. Numerous trials that followed have looked for optimal age of initiation, dose and frequency [6][7][8][9][10][11][12]31]. Conclusions, to date, are that prednisone 0.75 mg/kg/day and deflazacort 0.9 mg/kg are equally effective in improving muscle strength and function in the short term (6 months to 2 years), and that prednisone 0.75 mg/kg/day is optimal compared to other class I dosing studies (1.5, 0.3 mg/kg/day and 0.75 mg/kg/q.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…o.d. and 10 mg/kg/week) [6][7][8][9][10][11][12]31]. In these short-term treatment trials, adverse effects (weight gain, cushingoid appearance) were similar between studies.…”
Section: Corticosteroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic administration of glucocorticoids leads to relatively rapid muscle loss via the Forkhead box O (FOXO)/atrogin atrophy signaling pathway, and can cause glucocorticoid myopathy (critical care myopathy) (Di Giovanni et al, 2004;Puthucheary et al, 2010). In contrast, chronic glucocorticoids are used in Duchenne muscular dystrophy to increase muscle strength and prolong ambulation, possibly through their antiinflammatory effect (Bach et al, 2010;Hussein et al, 2010;Escolar et al, 2011). The beneficial properties of steroids are offset partly by side effects, including atrogin-mediated muscle wasting bone fragility, obesity, and short stature (Schara et al, 2001).…”
Section: Introductionmentioning
confidence: 99%